Nutrient status and forms of potassium in farmed soils at University of Benin - Efenudu, I. U. (2024)
This study was conducted to determine the nutrient status and forms of potassium in farmed soils at the University of Benin. The soil sample was collected from the Experimental Farm Site and control site at a depth of 0 cm - 15 cm, 15 cm - 30 cm, and 30 cm - 45 cm using a soil auger. Soils collected from each depth were air-dried, crushed, and sieved. The sieved samples were analyzed for some physical and chemical properties using standard laboratory procedures. The data obtained were analyzed by Genstat computer package at a 5 % probability. The result showed that the sand (833.9 g.kg-1) fraction was predominant in the experimental farm site. The pH (4.58) result was recorded in the experimental farm site compared to the control site (4.35). The result showed that (0.13 mg.kg-1) water soluble potassium (H2OK) was recorded in soil depth of 0 cm - 15 cm. The result showed that exchangeable potassium (Exch K) (0.17 mg.kg-1) at the Experimental Farm site is superior to the control site (0.12 mg.kg-1). The mean result of HCl K (0.37 mg.kg-1), Acid K (0.13 mg.kg-1), Residual K (0.45 mg.kg-1), and Total K (1.35 mg.kg-1) of the Experimental Farm site were superior to the control site HCl K (0.3 mg.kg-1), Acid K (0.12 mg.kg-1), Residual K (0.39 mg.kg-1) and Total K (1.18 mg.kg-1) respectively.  The result showed that forms of potassium, H2O K, exch K, HCl K, acid K, residual K, and total K exhibited positive correlations with EC, organic matter (O.M), total nitrogen (T. N), sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), and average phosphorus (Av. P).